Corrosion of N10276 in a H2S, HCl, and CO2 Containing Atmosphere at 480 °C and 680 °C - Manuela Nimmervoll; Gregor Mori; Edith Bucher; Alexander Schmid; Roland Haubner (Metals, 2021)
In several industrial processes, metallic materials suffer from chlorine- and sulfur-induced high-temperature corrosion. In previous studies, several steels have been tested at laboratory scale in a simulated gas atmosphere of a pyrolysis process of anthropogenic resources. In this paper, we propose a model on the course of corrosion in a H2S and HCl-containing atmosphere for N10276, which contains, besides iron, chromium, and nickel, also molybdenum as main alloying element. Bearing in mind the impact of the main alloying elements, as well as thermodynamic considerations and kinetic effects, the corrosion behavior of N10276 in a H2S and HCl-containing atmosphere at 480 °C and 680 °C can be explained. In addition, the corrosion behavior of N10276 is compared with earlier tested Fe-Cr-Ni alloys and differences in the corrosion behavior are stated within this paper.